Review of some existing shariah-compliant cryptocurrency / Ahmed Aliyu … [et al.] - Aliyu, Ahmed; Abu Bakar, Kamalrulnizam; Matsuda, Gen; Darwish, Tasneem S. J.; Abdullah, Abdul Hanan; Ismail, Abdul Samad; Raja Mohd. Radzi, Raja Zahilah; Yusof, Ahmad Fadhil; Mohamad, Mohd Murtadha; Idris, Mohd Yazid; Ismail, Zuhaimy; Yaacob, Ahmad Che (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2020)
Cryptocurrency has emerged as the most promising digital asset, which serves as a medium of exchange with distributed control and highly secured financial system. This lead to an increase in stakeholders’ interest in digital currency investment. The cryptocurrencies majorly involve two phases including Initial Coin Offering (ICO) and blockchain creation. These phases have been challenged with criticisms in terms of the Islamic shariah injunctions. These criticisms are based on two fundamental issues including whether cryptocurrency is backed by asset and has a regulatory authority or not. These issues are related to uncertainty, volatility and high speculation of the cryptocurrencies. Although, several cryptocurrencies claimed to have considered the shariah requirements in their proposed cryptocurrency ecosystems. However, a strict analysis of some of the existing cryptocurrencies reveals otherwise. Therefore, this paper presents a review of some shariah-compliant cryptocurrencies focusing on their volatility and speculation. The operations of cryptocurrencies need to follow the Islamic shariah requirements. The proposed review provides an insight regarding the acclaimed shariah-compliant cryptocurrencies to assess whether they comply with the shariah requirements or not.